Exclusion of bacterial co-infection in COVID-19 using baseline inflammatory markers and their response to antibiotics. (19th January 2021) - Mason, Claire Y; Kanitkar, Tanmay; Richardson, Charlotte J; Lanzman, Marisa; Stone, Zak; Mahungu, Tabitha; Mack, Damien; Wey, Emmanuel Q; Lamb, Lucy; Balakrishnan, Indran; Pollara, Gabriele
Abstract: Background: COVID-19 is infrequently complicated by bacterial co-infection, but antibiotic prescriptions are common. We used community-acquired pneumonia (CAP) as a benchmark to define the processes that occur in bacterial pulmonary infections, testing the hypothesis that baseline inflammatory markers and their response to antibiotic therapy could distinguish bacterial co-infection from COVID-19. Methods: Retrospective cohort study of CAP (lobar consolidation on chest radiograph) and COVID-19 (PCR detection of SARS-CoV-2) patients admitted to Royal Free Hospital (RFH) and Barnet Hospital (BH), serving as independent discovery and validation cohorts. All CAP and >90% COVID-19 patients received antibiotics on hospital admission. Results: We identified 106 CAP and 619 COVID-19 patients at RFH. Compared with COVID-19, CAP was characterized by elevated baseline white cell count (WCC) [median 12.48 (IQR 8.2–15.3) versus 6.78 (IQR 5.2–9.5) ×10 6 cells/mL, P <  0.0001], C-reactive protein (CRP) [median 133.5 (IQR 65–221) versus 86.0 (IQR 42–160) mg/L, P <  0.0001], and greater reduction in CRP 48–72 h into admission [median ΔCRP −33 (IQR −112 to +3.5) versus +14 (IQR −15.5 to +70.5) mg/L, P <  0.0001]. These observations were recapitulated in the independent validation cohort at BH (169 CAP and 181 COVID-19 patients). A multivariate logistic regression model incorporating WCC and ΔCRP discriminated CAP from COVID-19 with AUC 0.88 (95% CI 0.83–0.94). Baseline WCC >8.2 × 10 6 cells/mL or falling CRP identified 94% of CAP cases, and excluded bacterial co-infection in 46% of COVID-19 patients. Conclusions: We propose that in COVID-19, absence of both elevated baseline WCC and antibiotic-related decrease in CRP can exclude bacterial co-infection and facilitate antibiotic stewardship efforts.